Organic dairy farming in Uttarakhand: an analysis of prospect from farmersâ€™ perspective - MAJI, SAIKAT; Meena, Brajendra Singh (Indian Journal of Dairy Science, 2018)
AbstractOrganic dairy farming is getting increasingly popular among the farmers throughout the world. The declining trend of quality of natural resources and presence of pollutants in food chain as a result of decades long external chemical input based intensive farming has led to the recent re-emergence of interest in organic farming. Uttarakhand, one of the leading states in Organic farming in India, have a predominance of mostly traditional integrated crop livestock farming closed to organic system along with relatively unpolluted ecosystem. The state also have a vast number of certified organic crop farmers supported by well developed organizational structure for promoting organic farming as well as marketing of organic crop products. The present study analyzed the prospect of adopting certified organic dairy farming by these organic farmers like their crop farming component in terms of strengths, weaknesses, opportunities and threats. Analytical Hierarchy Process was utilized two quantify the factors, based on prevailing field level situation, under above four dimensions. It was found that â€œhuge natural resource base to ensure feed and water availabilityâ€ was the most important strength factor (with a global priority score of 0.084); whereas â€œlow productivity of indigenous breeds and production lossâ€ with global priority of 0.091, â€œeasy convertibility of traditional and integrated crop livestock based farming system to organic systemâ€ (global priority score 0.113) and â€œlack of organized certification system and certification standards for organic dairyâ€ (global priorityÂ  score 0.071) was the most important weakness, opportunity and threat factor respectively.Â